Legal Framework Of Investment: An Analysis Of Challenges And Its Implications For Economic Growth - Angga Saputra; Patricia Grace Dela Meifina Sibarani (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
Investment law plays a critical role in shaping economic performance by influencing investor confidence, capital allocation, and long term development outcomes. This study examines the legal framework governing investment in Indonesia, analyzes the principal challenges affecting its implementation, and evaluates its implications for economic growth. The research employs a normative juridical approach based on doctrinal legal analysis, conceptual examination, and qualitative interpretation of statutory regulations, academic literature, and policy documents related to investment governance. The findings reveal that Indonesia has undertaken substantial regulatory reforms aimed at improving legal certainty, business efficiency, and investor protection through the Investment Law, risk based licensing mechanisms, and regulatory harmonization initiatives. Nevertheless, the effectiveness of these reforms continues to be constrained by regulatory fragmentation, institutional coordination challenges, administrative uncertainty, governance weaknesses, and emerging regulatory issues associated with digital transformation and sustainability requirements. The analysis further indicates that a strong investment legal framework contributes to foreign direct investment attraction, capital formation, industrialization, employment creation, financial development, and long term economic competitiveness. The study concludes that strengthening regulatory coherence, institutional effectiveness, and governance quality is essential for maximizing the contribution of investment to sustainable and inclusive economic growth.